Pelatihan Umpire Judge dan Technical Official Cabang Olahraga Hockey Indoor - Salman, Salman; Hidayat, Teten; Riansyah, Riansyah; Wijaya, M Suma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to provide knowledge and training on increasing the competency of umpires, judges, and technical official s in indoor hockey. The methods used include theory sessions, discussions, presentations, and evaluation of participants' skills. The implementation of this community service is divided into two major activities, namely Focus Group Discussion (FGD), preparing instruments for participants' understanding of the rules of the hockey game with one validation resource. Meanwhile, training for referees, judges, and technical officials was carried out by 40 people from cities/districts throughout West Java that have Pengcab Hockey, inviting two resource persons. The results of this research found that for novice referees, all participants showed a significant increase in their understanding of the official rules and regulations of indoor hockey matches and were able to practice umpiring techniques well according to international standards, while for technical official s all were able to operate match equipment such as digital stopwatches, scores. Board, and a good communication system between officials, as well as understanding the procedures for recording match results and time management according to applicable rules. In conclusion, the Umpire Judge and Technical official Training for the indoor hockey sport held in West Java has had a positive impact in improving the quality and competency of sports leadership staff Keywords: Increasing the competence of umpires, judges, and technical official s